Pendampingan Membuat Mading Di Darul Ulum Tinggar Buntut Bangsal Mojokerto - Nursita, Dwi Indah; Rinda, Rinda; Mutoharoh, Mutoharoh; Utomo, Oqi Trimilanda; Nasikhah, Roudlotun (PUDAK: Local Wisdom Community Journal, 2023)
The motivation behind this assistance is to illustrate assistance in making wall magazines in various forms owned by MI Darul Ulum Tinggar Buntut Bangsal Mojokerto students. Wall magazines are the easiest type of mass correspondence media and are displayed on walls through well-arranged compositions and pictures so that they look interesting to look at and read. The making of this magazine is expected to build student excellence and imagination in skills. so that students are persuaded by their imaginative abilities to communicate life concerns that are reflected in life both in relation to the general habitat and everything that happens both real and imagined. The results obtained were that students were very enthusiastic about recording their imagination in hard copy form through a wall magazine by filling in every available rubric, both composition and images.